Constructs of Quality of Work Life: A Perspective of Information and Technology Professionals - Rethinam, Guna Seelan; Ismail, Maimunah (Eurojournals, 2007)
Many factors determine the meaning of quality of work life (QWL), one of which is work environment. A group of workforces that is greatly affected in QWL as a result of dynamic changes in work environment is information technology (IT) professionals. This article reviews the meaning of QWL, analyses constructs of QWL based on models and past research from the perspective of IT professionals in many countries and in Malaysia. The constructs of QWL discussed are health and well-being, job security, job satisfaction, competency development, work and non-work life balance. The article concludes that QWL from the perspective of IT professionals is challenging both to the individuals and organizations. The implications of this meaning and constructs for future research in QWL from the perspective of IT professionals are discussed.